Motivasi Belajar Siswa Sekolah Dasar Di Kabupaten Manokwari - Y.p.karafir, ; A.girik Allo, ; M.r.maspaitella, ; T.m.suruan, ; J.aninam, (Pendidikan Sekolah Dasar, 2010)
In 2005 Manokwari Regency has 8,892 citizens aged 5-15 years old who have no access to education. One of the factors that influenced this figure is the low of the studying interest of children for going to school and the parents paradigm which assume that education is not an investment for the future. The motivation of Elementary students was influenced by externals factors, such as, education system, education budgeting; and internals factors such as, home studying facilities. The research method used in this article is descriptive method. The result of this research shows that the frequency of studying in the city area is higher than in rural area. The same condition is happen at the students attendance factor in class and in the supporting facilities at home. In addition, the independency for home studying is significantly depending on homework that given by schools.